Pendampingan Diversifikasi Pangan Olahan Jagung Berbasis "Less Waste" pada Kelompok Wanita Tani di Desa Kersikan Pasuruan - Deny Utomo; Khoirin Maghfiroh; Sri Karuniari Nuswardhani (GUYUB: Journal of Community Engagement, 2024)
Corn is a primary commodity in Kersikan Village, cultivated by farmer groups. However, corn processing into food products has not yet been optimized, and current practices often result in waste due to limited knowledge among members of the Women Farmers Group (Kelompok Wanita Tani or KWT). Sustainable assistance is therefore needed to enhance their skills and knowledge. Through ongoing assistance, corn can be diversified into less-waste-based food products, where all parts of the corn are utilized to minimize processing waste. Corn kernels, for instance, are processed into dodol (a local confectionery) and tortilla chips, capitalizing on the nutritional content of corn, which includes carbohydrates, protein, fat, and various vitamins and minerals. Corn silk waste is used to make corn silk tea, which contains phenolic compounds with antioxidant properties. Additionally, corn husks are repurposed as natural packaging for the dodol. This sustainable processing activity engages KWT Permata from Kersikan Village, Gondang Wetan District, Pasuruan Regency, in stages that include socialization, training, technology application, and continued assistance and evaluation. This ongoing assistance model improves partners' knowledge, skills, and understanding in diversifying corn processing with a less-waste approach.